Analisis Kepuasan Pengguna Website TVCCTube Menggunakan Metode Webqual 4.0 - Nurul Ayuni Jingga Putri; Resad Setyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Citiasia and Sisfo Indonesia introduced a satellite-based television platform, namely TVCC (TV Co-Creation). In its current development, TVCC focuses on developing regional potential through digital channels and already has 2 main websites, namely tvcc.tv and also TVCCtube. TVCCTube is used as a forum for the government, public agencies and content creators to provide information about their respective regions to the public. Therefore it is necessary to evaluate periodically to maintain the quality of this tvcctube website. The data collection method in this study was by making observations at TVCC and also distributing questionnaires to Citiasia's mentors and mentees and the respondents for this study were 13 respondents. The analytical method used is the WebQual 4.0 method by testing the validity and reliability of each variable, namely usability quality, information quality, and interaction quality. Data analysis used in this study is to use SmartPLS 4 because it is very suitable for a limited sample. The results of the analysis that has been processed show that the quality of the TVCCtube website is 76.2% and the WebQual variable that most influences user satisfaction is usability quality with a total of 65.2%.